Description of the Learning Environment in Traditional Dance Training at the Sanggar Palinggam Bungo Pasang - Suci Ramadani; Solfema Solfema (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2021)
This research was motivated by the high participation of participants in traditional dance training at Sanggar Palinggam Bungo Pasang, Pesisir Selatan Regency. This study aims to see the description of the physical environment and social environment in traditional dance training at Sanggar Palinggam. This type of research is descriptive quantitative. The population of this study are 20 participants. Sample of the study are 16 people. The instruments of data collections are questionnaire with a statement, while the result of the research used percentage calculation. This result describe that learning environment of traditional dance at Sanggar Palinggam Bungo Pasang Pesisir selatan regency are 1) physic environment is good. It means that environment is suibtable with the instrument that the trainees need for training traditional dance. It can from the way of the trainer teach the trainee, also the trainer can give a conditional place with a pleasant training atmosphere and there is good air circulation, 2) the social environment is good. There is good interaction and communication between the trainee and their trainer. Then, it can be seen that every trainer has good communication each others. Good communication from the trainer can be seen that the trainer never say bad words in front of the trainee. The dance traditional learning always open with praying and greeting.Keywords: Learning Environment, Dance Training